Relationship Banking and SMEs: A Theoretical Analysis - Timo Baas; Mechthild Schrooten (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
Reliable information on small and medium sized enterprises (SMEs) is rare and costly for financial intermediaries. To compensate for this, relationship banking is often considered as the appropriate lending technique in the case of SMEs. In this paper we offer a theoretical model to analyze the pricing behavior of banks in a Bertrand competition framework with monitoring costs. We show that the lack of reliable information leads to comparably high interest rates even if a long-term relationship between borrower and bank exists. The paper offers a theoretical explanation why SME managers consider external finance as a major constraint to their business. (101 words)
Keywords: G21; D82; D43; M41; 330; Relationship Banking; Financial Constraints; Small and Medium Sized Enterprises; Accounting; Klein- und Mittelunternehmen; Verschuldungsrestriktion; Kreditgeschäft; Theorie